(untitled) (Research, Society and Development, 2024)
Introduction: New Delhi Metallo-β-lactamase (NDM) producing bacteria are resistant to carbapenem antibiotics, making them significant in the field of healthcare. Objective: To investigate the prevalence of NDM-producing bacteria in colonization/infections among patients in a public health service and to develop educational material aimed at enhancing healthcare professionals’ knowledge on prevention measures. Method: An observational prevalence epidemiological study was conducted, with data collected cross-sectionally using the TASY system. Descriptive analysis identified the epidemiological profile and some frequencies. In the statistical analysis, dependent variables were the species of microorganism and the focus of infection; independent variables included length of hospitalization, ventilator use, catheter-associated infections, and patient outcomes. After processing the data, educational material was produced for healthcare staff. Results: A total of 24 cases of NDM-producing bacteria infections were identified in the service. The most affected profile was men under 60 years with comorbidities. Infections among women, elderly individuals (>60 years), and patients with comorbidities were more likely to result in death. Klebsiella pneumoniae was the most frequently isolated NDM producer in the service, and the most prevalent infection focus was the urinary tract. Ventilator use and previous infections were significant predictors of the development of these bacteria. Conclusion: The epidemiological profile found in the study aligns with the literature on the subject. These microorganisms are spreading, requiring preventive actions to control their dissemination.